Clinical magnetic hyperthermia requires integrated magnetic particle imaging. (3rd March 2022) - Healy, Sean; Bakuzis, Andris F.; Goodwill, Patrick W.; Attaluri, Anilchandra; Bulte, Jeff W. M.; Ivkov, Robert
Abstract: Magnetic nanomaterials that respond to clinical magnetic devices have significant potential as cancer nanotheranostics. The complexities of their physics, however, introduce challenges for these applications. Hyperthermia is a heat‐based cancer therapy that improves treatment outcomes and patient survival when controlled energy delivery is combined with accurate thermometry. To date, few technologies have achieved the needed evolution for the demands of the clinic. Magnetic fluid hyperthermia (MFH) offers this potential, but to be successful it requires particle‐imaging technology that provides real‐time thermometry. Presently, the only technology having the potential to meet these requirements is magnetic particle imaging (MPI), for which a proof‐of‐principle demonstration with MFH has been achieved. Successful clinical translation and adoption of integrated MPI/MFH technology will depend on successful resolution of the technological challenges discussed. This article is categorized under: Therapeutic Approaches and Drug Discovery > Nanomedicine for Oncologic Disease Diagnostic Tools > In Vivo Nanodiagnostics and Imaging Abstract : A combined magnetic fluid hyperthermia (MFH), magnetic particle imaging (MPI), and magnetic nanoparticle thermometry (MNT) or MPI‐MFH‐MNT system improves on current MFH by imaging magnetic nanoparticles in tissues with MPI for thermal dose treatment planning. Subsequently, a treatment can be executed to a plan having defined thermal dose contours within the segmented treatment volume using real time thermometry with MNT to modulate MFH power for successful energy regulation and reproducible treatments. Histology image in top left is a photo of a human prostate tumor (DU145) subcutaneous xenograft grown in a male nude mouse that had been injected directly with MIONPs and subsequently stained with Prussian blue. See Hedayati et al. (2013) for details.